Lao People's Democratic Republic : Third Review under the Poverty Reduction and Growth Facility, and Requests for Waiver of Performance Criterion and Extension of the Arrangement. (IMF Staff Country Reports; Country Report ;, 2003)
Lao People's Democratic Republic (Lao PDR) showed commendable growth owing to its strong macroeconomic performance and structural reforms under the economic program. Executive Directors commended the fiscal performance, bank restructuring, and the private sector developments, and stressed the need to strengthen monetary and exchange rate policies. They welcomed the poverty reduction strategy and emphasized the need to accelerate structural reforms. They agreed that Lao PDR successfully completed the third review under the Poverty Reduction and Growth Facility (PRGF), and approved a waiver and an extension of the PRGF arrangement.